Quantifying the effect of interpregnancy maternal weight and smoking status changes on childhood overweight and obesity in a UK population-based cohort - Taylor, EJ; Ziauddeen, N; Berrington, A; Godfrey, KM; Alwan, NA (Public Library of Science, 2024)
Background: Maternal preconception and pregnancy exposures have been linked to offspring adiposity. We aimed to quantify the effect of changes in maternal weight and smoking status between pregnancies on childhood overweight/obesity (≥ 85th centile) and obesity (≥ 95th centile) rates in second children. Methods: Records for 5612 women were drawn from a population-based cohort of routinely collected antenatal healthcare records (2003–2014) linked to measured child body mass index (BMI) age 4–5 years. We applied the parametric G-formula to estimate the effect of hypothetical changes between pregnancy-1 and pregnancy-2 compared to the natural course scenario (without change) on child-2 BMI. Results: Observed overweight/obesity and obesity in child-2 at age 4–5 years were 22.2% and 8·5%, respectively. We estimated that if all mothers started pregnancy-2 with BMI 18·5–24·9 kg/m² and all smokers stopped smoking, then child-2 overweight/obesity and obesity natural course estimates of 22.3% (95% CI 21.2–23.5) and 8·3% (7·6–9·1), would be reduced to 18.5% (17.4–19.9) and 6.2% (5.5–7.0), respectively. For mothers who started pregnancy-1 with BMI 18·5–24·9 kg/m², if all smokers stopped smoking, child-2 overweight/obesity and obesity natural course estimates of 17.3% (16.0–18.6) and 5·9% (5·0–6·7) would be reduced to 16.0% (14.6–17.3) and 4·9% (4·1–5·7), respectively. For mothers who started pregnancy-1 with BMI ≥30 kg/m², if BMI was 18·5–24·9 kg/m² prior to pregnancy-2, child-2 overweight/obesity and obesity natural course estimates of 38.6% (34.7–42.3) and 17·7% (15·1–20·9) would be reduced to 31.3% (23.8–40.0) and 12.5 (8.3–17.4), respectively. If BMI was 25.0–29.9 kg/m² prior to pregnancy-2, these estimates would be 34.5% (29.4–40.4) and 14.6% (11.2–17.8), respectively. Conclusion: Interventions supporting women to lose/maintain weight and quit smoking between pregnancies could help reduce rates of overweight/obesity and obesity in second children. The most effective interventions may vary by maternal BMI prior to the first pregnancy.